Design and Build a Payment System in the Management Unit Rumah Susun IV - Anwar, Rafi; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2023)
Flat IV Manager is a unit formed by the government with the aim of creating flats that are comfortable, safe and provide convenience to each occupant. Flats IV Management Unit continues to strive to improve service and quality standards for its residents. the payment process is not efficient because it takes a long time to process payments and input payment data, and also conventional payments are considered insecure for users. Transaction data processing has not been done automatically, data entry is still using MS. Excel so it takes a relatively long time. Conducted research on the Payment Information System in the IV managing unit of the flat, Designing and manufacturing a web-based payment information system in the IV managing unit of the flat. To find out how the implementation and benefits of web-based payments in the management unit of flats IV. Based on the results of the research and discussion, it can be concluded that it has answered the existing problems. This system makes the payment process at the IV Flats Management Unit computerized in one database so that the delivery of information and data search will be more optimal. Functionally, the design created is a web-based payment data tracking application design, which is tailored to user needs. This system is also a supporting tool that can facilitate the work of Admin Staff in processing payment data, preparing payment reports, and making it easy for tenants to process the registration of apartment occupants.